The Influence of the Quality of Human Resources on Employee Performance at the Biringbulu Sub-District Office Gowa Regency - Sulfikar; Naidah; Nurinaya (IECON: International Economics and Business Conference, 2023)
This study aims to determine whether the quality of human resources has a significant effect on employee performance at the Biringbulu sub-district office, Gowa district. The type of research used is quantitative analysis method with a sample of 32 respondents. The data collection technique used is the questionnaire distribution technique. This study uses a simple linear regression analysis method. The results of this study indicate that, based on the t-statistical test, the t-count value is 6.632 with a significant level of t of 0.00 < 0.05. So that the influence of the quality of human resources has a positive value, which means that the quality is concluded that the quality of human resources has a positive and significant effect on employeeperformance.